Calisthenics with words: The effect of readability and investor sophistication on investors' performance judgment - Xiao Carol Cui (International Journal of Financial Studies, 2016)
Since the 1990s, the SEC has advocated for financial disclosures to be in "plain English" so that they would be more readable and informative. Past research has shown that high readability is related to more extreme investor judgments of firm performance. Processing fluency is the prevalent theory to explain this: higher readability increases the investor's subconscious reliance on the disclosure, so positive (negative) news leads to more positive (negative) judgments. The relationship may not be so simple, though: drawing on research from cognitive psychology, I predict and find that investor financial literacy simultaneously influences investor decision-making, and that it has an interactive effect with readability. When presented with financial disclosure containing conflicting financial information, investors with higher financial literacy make more negative judgments than investors with low financial literacy when the disclosure is easy to read, but the effect becomes insignificant when the disclosure becomes difficult to read. This effect is moderated by a comprehension gap between the two investor groups. Financial literacy and readability interact to impact both how and how well the investor processes financial information.
Keywords: G02; 330; readability; financial literacy; management disclosures; textual information; investor decision-making